PD-L1+ Regulatory B Cells Are Significantly Decreased in Rheumatoid Arthritis Patients and Increase After Successful Treatment - Zacca, Estefanía R.; Onofrio, Luisina I.; Acosta, Cristina D. V.; Ferrero, Paola V.; Alonso, Sergio M.; Ramello, María C.; Mussano, Eduardo; Onetti, Laura; Cadile, Isaac I.; Stancich, Maria I.; Taboada Bonfanti, Maria C.; Montes, Carolina L.; et al. (Frontiers in Immunology, 2018)
Background: B cells play an important role in the development and maintenance of rheumatoid arthritis (RA). Although IL-10–producing B cells represent a major subset of regulatory B cells (Bregs) able to suppress autoimmune and inflammatory responses, recent reports showed that B cell-mediated immune suppression may also occur independent of IL-10. For instance, B cells can modulate T cell immune responses through the expression of regulatory molecules such as PD-L1. So far, PD-L1-expressing B cells have not been analyzed in RA patients. Objective: To analyze the frequency of PD-L1-expressing B cells in the peripheral blood of RA patients compared to healthy controls (HC) matched for sex and age, their function on T cell response and their changes in response to therapy. Methods: Fresh peripheral blood B cells from RA patients and HC were characterized by flow cytometry and their functionality assessed in a co-culture system with autologous T cells. Results: The frequencies of CD19+PD-L1+ B cells, CD24hiCD38-PD-L1+ and CD24hiCD38hiPD-L1+ B cells were significantly lower in untreated RA patients than in HC. In a follow-up study, the frequencies of PD-L1+ B cells (CD19+PD-L1+ B cells, CD24hiCD38-PD-L1+ and CD24hiCD38hiPD-L1+ B cells) increased significantly after treatment in good responder patients, although the frequency of total CD24hiCD38hi B cells decreased. CD19+ B cells from untreated RA patients and HC upregulated PD-L1 expression similarly upon stimulation with CpG plus IL-2 and were able to suppress CD8+ T cell proliferation and cytokine production in a PD-L1-dependent manner. Conclusions: Our results show that PD-L1+ B cells exhibiting T cell suppressive capacity are significantly decreased in untreated RA patients but increase in response to successful treatment. PD-L1 expression on B cells from RA patients can be modulated in vitro and PD-L1+ B cells could thus provide new perspectives for future treatment strategies.